Aspects influencing the foreign exchange reserves of Indonesia - Purba, Andreas Sendy; Tiawon, Harin; Beatris, Diana (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2023)
Analysis of Factors Affecting Indonesia's Foreign Exchange Reserves using the Error Correction Model (ECM) Approach. This study aims to determine and analyze the effect of American interest rates, Indonesian interest rates, foreign debt, the rupiah exchange rate, net exports and foreign investment on Indonesia's foreign exchange reserves in 1991-2022. The data used in this study is time series data, using secondary data obtained from the publication of the official websites of Bank Indonesia, the World Bank and the Central Bureau of Statistics, totaling 32 years. The analysis technique used in this study is the error correction model with the Eviews 10 tool. The results of this study indicate that in the long term, American interest rates and Indonesian interest rates have a negative effect on Indonesia's foreign exchange reserves. Foreign debt, rupiah exchange rate and net exports have a positive influence on Indonesia's foreign exchange reserves. Meanwhile, foreign investment has no effect on Indonesia's foreign exchange reserves. In the short term, American interest rates, Indonesian interest rates, rupiah exchange rates, net exports and foreign investment have no effect on Indonesia's foreign exchange reserves. Meanwhile, foreign debt has a positive effect on Indonesia's foreign exchange reserves